Recommendations of Gentamicin Dose Based on Different Pharmacokinetic/Pharmacodynamic Targets for Intensive Care Adult Patients: A Redefining Approach - Abbasi MY; Chaijamorn W; Wiwattanawongsa K; Charoensareerat T; Doungngern T (Dove Medical Press, 2023)
Mohammad Yaseen Abbasi,1 Weerachai Chaijamorn,2 Kamonthip Wiwattanawongsa,1 Taniya Charoensareerat,3 Thitima Doungngern1 1Department of Clinical Pharmacy, Faculty of Pharmaceutical Sciences, Prince Songkla University, Hat Yai, Songkhla, 90110 Thailand; 2Department of Pharmacy Practice, Faculty of Pharmaceutical Sciences, Chulalongkorn University, Pathum Wan, Bangkok, 10330, Thailand; 3Faculty of Pharmacy, Siam University, Bangkok, 10160, ThailandCorrespondence: Thitima Doungngern, Department of Clinical Pharmacy, Faculty of Pharmaceutical Sciences, Prince of Songkla University, Hat Yai, Songkhla, 90110, Thailand, Tel +66-74288877, Fax +66-74428222, Email dthitima@pharmacy.psu.ac.thBackground: In addition to the maximum plasma concentration (Cmax) to the minimum inhibitory concentration (MIC) ratio, the 24-hour area under the concentration-time curve (AUC24h) to MIC has recently been suggested as pharmacokinetic/pharmacodynamic (PK/PD) targets for efficacy and safety in once-daily dosing of gentamicin (ODDG) in critically ill patients.Purpose: This study aimed to predict the optimal effective dose and risk of nephrotoxicity for gentamicin in critically ill patients for two different PK/PD targets within the first 3 days of infection.Methods: The gathered pharmacokinetic and demographic data in critically ill patients from 21 previously published studies were used to build a one-compartment pharmacokinetic model. The Monte Carlo Simulation (MCS) method was conducted with the use of gentamicin once-daily dosing ranging from 5- 10 mg/kg. The percentage target attainment (PTA) for efficacy, Cmax/MIC ~8- 10 and AUC24h/MIC ≥ 110 targets, were studied. The AUC24h > 700 mg⋅h/L and Cmin > 2 mg/L were used to predict the risk of nephrotoxicity.Results: Gentamicin 7 mg/kg/day could achieve both efficacy targets for more than 90% when the MIC was < 0.5 mg/L. When the MIC increased to 1 mg/L, gentamicin 8 mg/kg/day could reach the PK/PD and safety targets. However, for pathogens with MIC ≥ 2 mg/L, no studied gentamicin doses were sufficient to reach the efficacy target. The risk of nephrotoxicity using AUC24h > 700 mg⋅h/L was small, but the risk was greater when applying a Cmin target > 2 mg/L.Conclusion: Considering both targets of Cmax/MIC ~8- 10 and AUC24h/MIC ≥ 110, an initial gentamicin dose of 8 mg/kg/day should be recommended in critically ill patients for pathogens with MIC of ≤ 1 mg/L. Clinical validation of our results is essential.Keywords: gentamicin, Cmax/MIC, AUC24h/MIC, nephrotoxicity, critically ill